CITREX showcased 179 UMP’s research works - UMP, PNC
Universiti Malaysia Pahang (UMP) displayed 179 research projects produced by its undergraduates and lecturers in a move to nurture creativity and innovation as well as to acculturate research that would contribute to the nation’s future technology.